ClassEscape : The Conceptual Design of Crowd Modeling in Fire Evacuation Simulation - Nur Aida Suraya, A Razak; Hamizan, Sharbini; Chiu, Po Chan; Noor Hazlini, Borhan; Cheah, Wai Shiang (2024)
In the contemporary era, the proliferation of various applications, notably crowd modeling, has revolutionized problem-solving approaches across diverse sectors. However, the absence of organized fire drills poses a significant challenge to navigating hazardous zones to safety, particularly within densely populated lecture halls. To tackle these challenges, this paper presents the conceptual development of an evacuation simulation framework. The framework aims to propose a pseudo-code for path selection with a graphical interface tailored for simulating fire emergency evacuations, specifically within lecture halls or theaters. Utilizing 2D/3D model simulations, the framework seeks to replicate crowd evacuation scenarios with varying fire locations, providing valuable insights for enhancing fire safety measures and emergency response strategies. The significance of this project lies in its potential to educate and prepare students and staff in Faculty of Computer Science and Information Technology (FCSIT) teaching and learning facilities for making informed decisions during fire emergencies, thereby improving overall safety and preparedness. This conceptual design serves as a foundational step towards developing a comprehensive simulation tool for effective fire evacuation planning in educational institutions.